Induced Mitophagy Promotes Cell Cycle Re-Entry in Adult Cardiomyocytes - Rafeeq P. H. Ahmed; Onur Kanisicak; Perwez Alam (Cells)
Background: The limited regenerative capacity of adult mammalian cardiomyocytes (CMs) poses a significant challenge for cardiac repair following myocardial infarction. In contrast to adult mammals, CMs in zebrafish and newt hearts retain a lifelong capacity for proliferation and cardiac regeneration. Likewise, neonatal mice exhibit a brief postnatal period, during which CMs retain the ability to proliferate and contribute to myocardial repair, which markedly diminishes within the first week of life. Emerging evidence indicates that adult CM cell cycle progression is critically influenced by oxidative stress. Adult mammalian CMs possess a high mitochondrial content to meet their substantial energy demands. However, this also leads to elevated reactive oxygen species (ROS) production, resulting in DNA damage and subsequent cell cycle arrest. We hypothesize that reducing the mitochondrial content in adult CMs will mitigate ROS production, thereby facilitating cell cycle progression. Methods: Adult CMs were isolated from adult rats (≥12 weeks old). To induce mitophagy, adult CMs were transfected with parkin-expressing plasmid and then treated with carbonyl cyanide 3-chlorophenylhydrazone (CCCP), a mitochondrial protonophore, for 7 days. Post-treatment assessments included the quantification of adult CM proliferation, mitochondrial content, and ROS levels. Results: CCCP-treated adult CMs exhibited a significant increase in proliferation markers, including EdU incorporation, KI67, phospho-histone H3, and Aurora B. Furthermore, CCCP treatment significantly reduced the mitochondrial content, as evidenced by decreased MitoTracker, TMRM, and Tom20 staining compared to controls. This was accompanied by electron microscopy analysis, which showed a significant reduction in the mitochondrial number in the adult CM after CCCP treatment. Moreover, our results also demonstrate a marked reduction in oxidative stress, demonstrated by lower 123-dihydro-rhodamine (123-DHR), CellROX signals, and VDAC. Conclusions: Our findings demonstrate that CCCP-mediated mitochondrial depletion reduces oxidative stress and promotes cell cycle re-entry in adult CM. This study provides direct experimental evidence and substantiates the role of elevated mitochondria and ROS levels in adult CM cell cycle exit.